APPLICATION OF SHARIA ACCOUNTING IN MSMES: LITERATURE STUDY AND RESEARCH GAP - Tegar Fitria (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2026)
This study explores the application of sharia accounting in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia through a comprehensive literature review. Sharia accounting, based on the principles of the Qur’an and Hadith, emphasizes justice, transparency, and accountability in financial reporting, distinguishing it from conventional accounting systems. The research identifies that the implementation of sharia accounting among MSMEs remains low, primarily due to limited understanding, insufficient training, and lack of access to technology and standardized frameworks such as PSAK Syariah and SAK EMKM. Key challenges include human resource constraints, technological barriers, the dominance of conventional accounting paradigms, and inconsistent regulatory adoption. Despite these obstacles, the development and adoption of simplified, user-friendly, and digital-based sharia accounting systems present significant opportunities for MSMEs, particularly within Indonesia’s rapidly growing halal ecosystem. The study highlights a research gap in practical implementation and calls for collaborative efforts among government, academia, and industry to enhance literacy, provide targeted training, and develop adaptive policies. The findings serve as a foundation for future research and policy development aimed at increasing the adoption of sharia accounting, thereby promoting transparency, accountability, and sustainable business practices aligned with Islamic values in the MSME sector.